Reducing The “Justice Gap” Through Access to Unbundled Legal Services: Utilizing an A2J Measurement Framework to Measure Unbundling Effectiveness - Lowenberger, Brea; Selensky, Elaine; McCutcheon, Jessica (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2024)
The ever-growing disparity between the cost of legal services and Canadians’ ability to pay for those services is known as the “justice gap.” As that gap widens, stakeholders must look for innovative ways to address it. In recent years, the potential for lawyers to offer unbundled legal services [ULS] through limited scope retainers has received considerable commentary as a “person” or “user-centred” justice tool, largely based on increasing affordability. ULS may expand access to individuals that cannot afford full representation but do not qualify for government-funded legal aid. However, empirical research on ULS as an access-to-justice (A2J) tool in Canada has only begun. This article contributes to the growing discourse on measuring ULS and is novel in Canada in its examination of ULS effectiveness as an A2J tool in reference to an A2J Measurement Framework and sample survey data from a ULS pilot project in Saskatchewan, Canada. We also identify what we do not yet know about ULS efficacy and why we should care about these unknowns. We caution against some of the generalizations currently made in the literature about which individuals are best suited for ULS. Finally, we conclude with ideas on how to continue studying these unknowns in reference to the framework for more efficient evaluation and comparative ULS data across jurisdictions. Utilizing the framework to measure ULS effectiveness across jurisdictions could help determine whether such initiatives are working from an A2J view and making a difference in the overall movement to reduce the justice gap.